THU0001 Differential methylation as a potential biomarker of methotrexate response in patients with rheumatoid arthritis. (15th June 2017) - Nair, N; Plant, D; Verstappen, SM; Isaacs, JD; Morgan, AW; Hyrich, KL; Barton, A; Wilson, AG; ,
Abstract : Background: Methotrexate (MTX) is the first-line disease modifying anti-rheumatic drug for the treatment of rheumatoid arthritis (RA). However, many patients do not respond adequately or experience adverse effects 1, 2 ; therefore, identifying blood-based biomarkers that predict treatment response is a research priority. DNA methylation is an epigenetic marker that modifies but does not alter DNA sequence, and it is thought that MTX may act, at least in part, by inhibiting intracellular methyl donor transfer leading to DNA hypomethylation 2 . Objectives: We aimed to identify differential DNA methylation signatures in whole blood, which may act as biomarkers predictive of response to MTX in patients with RA. Methods: DNA methylation was measured using the HumanMethylation450 BeadChip in DNA samples from individuals recruited to the Rheumatoid Arthritis Medication Study (RAMS), a one year observational study in the UK including patients with RA starting MTX for the first time. In RAMS, demographic and clinical data are collected prior MTX start (baseline) and at 6 months after commencing MTX. DNA was extracted from whole blood samples collected baseline and at 4 weeks from patients who, at 6 months, had a EULAR good response (n=36) or EULAR poor response (n=36) to MTX. Differentially methylated positions (DMPs) between the baseline and 4 weeks, and between good and poor response were identified using linear regression, adjusting for gender, age, cell composition, baseline disease activity score (DAS28), and smoking status. Analyses also compared methylation with changes in DAS28 and the individual DAS28 components over 6 months. DMPs that showed significant differences in the test cohort were selected for replication by pyrosequencing in an independent group of 100 patients with both baseline and 4 week samples. Results: Based on percentage change in methylation between pre-treatment and following 4 weeks of therapy, two DMPs were significantly associated with response status in samples taken at 4 weeks (p-value <10 -5 ). Three additional DMPs were associated with change in tender joint count, whilst three other DMPs were associated with change in swollen joint count, and a further four DMPs associated with change in C-reactive protein. Of the four DMPs tested to date, hypermethylation at cg23700278 at baseline suggests replicated association with improvement in swollen joint count by 6 months. The nearest gene to the cg23700278 locus is adrenoceptor alpha 2C ( ADRA2C ), involved in neurotransmission. Conclusions: These preliminary results suggest DNA methylation may provide a biomarker of MTX response but requires replication in other data sets. References: Verstappen SMM et al. (2012) Int. J. Clin. Rheu. 7(5):559–567. Kim Y, et al. (1996) J. Lab.Clin.Med. 128:165–172. Disclosure of Interest: None declared